2013
DOI: 10.1530/rep-12-0324
|View full text |Cite
|
Sign up to set email alerts
|

Role of the cell cycle in regression of the corpus luteum

Abstract: The corpus luteum contains differentiated steroidogenic cells that have exited the cell cycle of proliferation. In some tissues, deletion of quiescent, differentiated cells by apoptosis in response to injury or pathology is preceded by reentry into the cell cycle. We tested whether luteal cells reenter the cell cycle during the physiological process of luteolysis. Ovaries were obtained after injection of cows with a luteolytic dose of prostaglandin F 2a (PGF). In luteal sections, cells co-staining for markers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
12
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 83 publications
1
12
0
1
Order By: Relevance
“…These observations support our earlier findings (Liptak et al 2005) that activated immune cells may contribute a factor (or factors) that impair steroidogenesis in response to LH. It is known that activated monocytes produce inflammatory cytokines, nitric oxide, and reactive oxygen species (Murray & Wynn 2011, Zhou et al 2014) all of which may contribute individually or in combination to the inhibition of progesterone synthesis (Al-Gubory et al 2012, Quirk et al 2013, Skarzynski et al 2013). In the in vivo setting, activated monocytes may also secrete matrix metalloproteinases that contribute to the degradation of the extracellular matrix (Murray & Wynn 2011), which could facilitate the recruitment of additional inflammatory cells to the regressing corpus luteum.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These observations support our earlier findings (Liptak et al 2005) that activated immune cells may contribute a factor (or factors) that impair steroidogenesis in response to LH. It is known that activated monocytes produce inflammatory cytokines, nitric oxide, and reactive oxygen species (Murray & Wynn 2011, Zhou et al 2014) all of which may contribute individually or in combination to the inhibition of progesterone synthesis (Al-Gubory et al 2012, Quirk et al 2013, Skarzynski et al 2013). In the in vivo setting, activated monocytes may also secrete matrix metalloproteinases that contribute to the degradation of the extracellular matrix (Murray & Wynn 2011), which could facilitate the recruitment of additional inflammatory cells to the regressing corpus luteum.…”
Section: Discussionmentioning
confidence: 99%
“…PGF has been shown to act indirectly at the vascular level to cause disruption of luteal capillaries (Maroni & Davis 2011) and apoptosis of capillary endothelial cells (Henkes et al 2008). PGF has also been implicated in the initiation of luteal cell apoptosis in vivo (Davis & Rueda 2002, Quirk et al 2013); however, PGF alone cannot directly reduce the viability of luteal cells in vitro (Davis & Rueda 2002, Kawaguchi et al 2013). Thus, other mechanisms must be activated for luteolysis to proceed through both the functional (loss of progesterone secretion) and structural (apoptosis and tissue remodeling) stages of regression.…”
Section: Introductionmentioning
confidence: 99%
“…It is interesting to note that differentiated, nonproliferating luteal cells show the presence of PCNA. Several previous studies also reported expression of cell proliferation markers PCNA or Ki67 during rat [ 38 ], mare [ 39 ] and cow [ 40 ] luteal regression. It is suggested that the decline in progesterone synthesis during natural CL luteolysis may promote re-entry of luteal cells into the cell cycle and susceptibility to apoptosis [ 40 ].…”
Section: Discussionmentioning
confidence: 76%
“…6 In addition to steroidogenic cells, the CL contains endothelial cells (EC), pericytes, fibroblasts and immune cells. [7][8][9] During the estrous cycle, the CL is developed from the ovulatory follicle and undergoes remarkable growth, differentiation and remodeling. 10 If an oocyte is not fertilized, the CL will regress, with apoptosis of luteal cells and a decline in P4 synthesis.…”
Section: Introduction Corpus Luteummentioning
confidence: 99%